Importance of Wells Score and Geneva Score for the evaluation of patients suspected of pulmonary embolism - Grüttner, Joachim; Walter, Thomas; Lang, Siegfried; Apfaltrer, Paul; Henzler, Thomas; Viergutz, Tim (In vivo, 2015)
Aim: The European Society of Cardiology guidelines for pulmonary embolism (PE) published in 2008 and updated in 2014 recommend a risk stratification including risk scores like Wells and the Geneva score. The utility and practicability of these scores are controversially discussed. Recently, in a trauma cohort and in spinal surgery patients, no correlation between Wells Score and PE diagnosis was found. The aim of the study was the evaluation of Wells and Geneva scores in patients presenting with chest pain, dyspnoea or syncope in an emergency department. Patients and Methods: We retrospectively examined 326 patients suspected of PE, including assessment, according to Wells and Geneva scores. Results: PE was detected in 13.5 %. The average Wells score was 1.0, the average Geneva score 3.9. The receiver operating characteristic (ROC) curve analyses showed for both scores a high significant area under the curve (Wells score 0.68; Geneva score 0.64). The association between the scores and the diagnosis of PE was calculated with logistic regression analysis and showed high significant odds ratios (OR) for both scores (Wells score 1.38; Geneva score 1.24). There was no significant difference between the area under the curve (AUC) of Wells score and Geneva score. Conclusion: The utility of Wells and Geneva scores for the evaluation of patients suspected of PE in an emergency patient cohort.
Gesehen am 20.10.2017